The Effectiveness of Behavioralconservation with Modeling Techniques Through Lasson Study to Improve Character of Fun for Others - I Gede Mahadi Yuda Priharta; I Ketut Dharsana; Ni Ketut Suarni (RedwhitePress)
The purpose of this study was to determine the effect of Ivan Pavlov's behavioral counseling with modeling techniques to enhance the character to please others. This type of research is quasi-experiment with pretest-posttest control group design. The sample of this study was 32 students who collected character of fun for others data using the character of fun for other questionnaire. This is evidenced by the value of tcount 4.07 > ttable 2.03 so Ho is rejected and Ha is accepted. So there are significant differences .So that it can be concluded that Ivan Pavlov's behavioral counseling with effective modeling techniques to enhance character pleases other students of class VIII1 of STATE 2 state high school singaraja.